MEDIA EXPOSURE AND SYMPATHETIC NERVOUS SYSTEM REACTIVITY PREDICT PTSD SYMPTOMS AFTER THE BOSTON MARATHON BOMBINGS. Issue 7 (July 2014) - Busso, Daniel S.; McLaughlin, Katie A.; Sheridan, Margaret A.
<x xml:space="preserve">Abstract</x> Background Terrorist attacks have been shown to precipitate posttraumatic stress disorder (PTSD) symptomatology in children and adolescents, particularly among youths with high exposure to media coverage surrounding such events. Media exposure may be particularly likely to trigger PTSD symptoms in youths with high physiological reactivity to stress or with prior psychopathology or exposure to violence. We examined the interplay between media exposure, preattack psychopathology, autonomic nervous system (ANS) reactivity, and prior violence exposure in predicting PTSD symptom onset following the terrorist attack at the 2013 Boston Marathon. Methods A community sample of 78 adolescents (mean age = 16.7 years, 65% female) completed a survey about the bombings, including media exposure to the event and PTSD symptoms. All respondents participated in a study assessing psychopathology prior to the attack, and sympathetic and parasympathetic reactivity to a laboratory‐based stressor was assessed in a subset (N = 44) of this sample. We examined the associations of media exposure, ANS reactivity, preattack psychopathology, and prior violence exposure with onset of PTSD symptoms related to the bombings. Results Media exposure, preattack psychopathology, and prior violence exposure were associated with PTSD symptoms. Moreover, media exposure interacted with sympathetic reactivity to predict PTSD symptom onset, such that adolescents with lower levels of sympathetic reactivity developed PTSD symptoms only following high exposure to media coverage of the attack. Conclusions We provide novel evidence that physiological reactivity prior to exposure to an unpredictable traumatic stressor predicts PTSD symptom onset. These findings have implications for identifying youths most vulnerable to PTSD following wide‐scale trauma.